The m6A Methyltransferase METTL14-Mediated N6-Methyladenosine Modification of PTEN mRNA Inhibits Tumor Growth and Metastasis in Stomach Adenocarcinoma - Yao, Qi; He, Lanzhen; Gao, Xucan; Tang, Na; Lin, Lifen; Yu, Xiaofang; Wang, Dong (Frontiers in Oncology, 2021)
Background: Stomach adenocarcinoma (STAD) is a common reason for tumor-related fatalities globally, as it results in distant metastasis. Methyltransferase-like 14 (METTL14), a notable RNA N6-adenosine methyltransferase (m6A) plays a significant role in the growth of tumor through controlling the RNA working. This study aims to highlight METTL14 in STAD’s biological function and molecular mechanism. Methods: Bioinformatics and immunohistochemical (IHC) assays have been utilized for the detection of METTL14 expression in the STAD. METTL14’s biological function have been shown while making a use of HGC-27 and AGS cells in vitro experiments. MeRIP-qPCR and luciferase reporter assays were employed for the exploration of METTL14’s mechanism modifying the target of phosphatase and tensin homologue (PTEN). Subcutaneous xeno transplantation model and STAD liver metastasis orthotopic tumor model were used to study METTL14 in STAD in vivo. Results: METTL14 expression was substantially downregulated in STAD reflecting contribution to major tumors, progressed TNM stage as well as poor overall survival (OS) in STAD. Moreover, METTL14’s inhibition of STAD cells proliferation, migration and invasion has been verified in vitro assays. Furthermore, an identification of PTEN being METTL14-mediated m6A modification’s substrate has been made. METTL14’s overexpression highly enhanced PTEN mRNA m6A variation, stabilized PTEN mRNA and increased protein. Further, it has been found out that METTL14-mediated STAD cells inhibition of proliferation and invasion dependent on PTEN. At last, we demonstrated that METTL14 inhibit STAD growth and metastasis in vivo models. Conclusions: METTL14 inhibits tumor growth and metastasis of STAD via stabilization PTEN mRNA expression. Therefore, METTL14 is a potential biomarker of prognosis and therapeutic targets for STAD.